2016
DOI: 10.18632/oncotarget.9683
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular alterations in olfactory neuroblastoma: implications for pathogenesis, prognosis and treatment

Abstract: Olfactory neuroblastoma (ONB, Esthesioneuroblastoma) is an infrequent neoplasm of the head and neck area derived from olfactory neuroepithelium. Despite relatively good prognosis a subset of patients shows recurrence, progression and/or metastatic disease, which requires additional treatment. However, neither prognostic nor predictive factors are well specified. Thus, we performed a literature search for the currently available data on disturbances in molecular pathways, cytogenetic changes and results gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 101 publications
(118 reference statements)
3
34
0
Order By: Relevance
“…A similar overlap in copy number alterations between neuroendocrine carcinoma of the salivary gland a lung has also been reported . Similarly, only few data on the mutational landscape of olfactory neuroblastoma are available with preferential affection of TP53 and a heterogeneous pattern of copy‐number alterations .…”
Section: Tumors Of the Sinonasal Tractsupporting
confidence: 60%
“…A similar overlap in copy number alterations between neuroendocrine carcinoma of the salivary gland a lung has also been reported . Similarly, only few data on the mutational landscape of olfactory neuroblastoma are available with preferential affection of TP53 and a heterogeneous pattern of copy‐number alterations .…”
Section: Tumors Of the Sinonasal Tractsupporting
confidence: 60%
“…This observation may explain the more aggressive biological behavior of ENB during childhood and the poor survival in our series. A recent study found that half of ENBs have clinically relevant genomic alteration, which are identified in different genes such as TP53 , PIK3CA , NF1 , CDKN2A , or CDKN2C . Recently, Classe et al reported an integrative multiomics analysis of ENB identifying two subgroups of ENBs: neural and basal .…”
Section: Discussionmentioning
confidence: 99%
“…Data from several CGH studies have shown the changes that include gains at 7q, 9p, 13q, 17q, 17p13, 20p/q, 22q, and Xp/q, and losses or deletions at 1p, 2q, 3p/q, 6q, 9p, 10p/q, 22q, and Xp/q, with high‐grade ENBs demonstrating more alterations than low‐grade tumors . None of these changes have been routinely observed, limiting their prognostic or diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies utilizing comparative genomic hybridization (CGH) have identified complex patterns of copy number abnormalities in ENB tumors, but few observations were consistent across studies , limiting generalizable conclusions and indicating that heterogeneous sets of alterations can drive ENB development. Even fewer studies have used DNA sequencing techniques to profile ENB , with three tumors in the literature evaluated by comprehensive sequencing methods . There are no mutations in ENB tumors reported in commonly used databases collating genomic cancer data, such as COSMIC, cBioPortal, and the ICGC portal.…”
Section: Introductionmentioning
confidence: 99%